A structural model to assess the impact of bank capitalization changes conditional on a bail-in versus bail-out regime - Marco Groß; Tomasz Dubiel-Teleszynski; Javier Población (European Central Bank (ECB), 2018)
We develop a structural model for valuing bank balance sheet components such as the equity and debt value, the value for the government when the bank is operated by private shareholders including the present value of a possible future bailout, the bailout value incurred by the government following the abandonment of the private shareholders, and, moreover, some price and risk parameters, including the funding cost spread and the banks'probability of default. The structural model implies an abandonment threshold, at which if total income drops below this threshold, private shareholders abandon the bank. In this case, the shareholders lose part (or all) of the capital that they hold in the bank, the creditors lose part or all of their debt, and the government receives a portion (or all) of the capital and all of the debt that is not recovered by creditors. Hence, we assume that part of the capital can be lost due to financial distress or to cover bankruptcy costs. We use the model framework to assess the impact of capital-based macro-prudential policy measures and focus in particular on assessing the difference that an assumed bail-in as opposed to bail-out regime can make.
Keywords: G21; G28; H81; 330; Structural model; abandonment trigger; bank bailout; capital-based macro-prudential policy